When colleagues come to see each other as rivals: Does internal competition affect workplace performance? - Felia Braun; Hendrik Sonnabend (Journal of Economics and Statistics, 2024)
We study workplace performance effects triggered by team-internal rivalry. Specifically, we focus on duos of goalkeepers in professional soccer competing for in-season playing time. Using performance data from the most prestigious European soccer leagues and tournaments, we provide evidence for asymmetric discouragement: While the ex ante underdog feels demotivated by internal rivalry, we cannot observe a comparable effect for the ex ante favourite. Moreover, we find that workplace competition generally works explicitly rather than implicitly, meaning that demonstrated performance outweighs pure skills when it comes to the emergence of peer effects. To address a potential endogeneity problem caused by non-random selection, we show that our results are robust to quasi-random rotations caused by (minor to moderate) injuries and bans.
Keywords: J44; L83; 330; competition; goalkeepers; internal rivalry; performance; soccer